Análisis de las redes sociales: Facebook y whatsapp en espacios estudiantiles como forma de intercambio de información social en la carrera de Comunicación Social de la Universidad Técnica de Babahoyo - Marquinez Crespo, Paul Fernando (2020)
This research work makes a breakthrough on the management of social networks within students of the social communication career of the Technical University of Babahoyo. The most used network in the world is Facebook, sequel to the WhatsApp application, For this it was necessary for the development a theoretical approach, which has to analyze the use of Facebook and WhatsApp as a resource of social information sharing, reference making new technologies and the new turn of communication in the digital age. So the analysis is based on these two applications. In the same way these applications have made extraordinary progress in the teaching/learning process, in their mode of communication within the classrooms.